Political paradigms and vocational education policy in Indonesia: a document analysis - Yasdin Yasdin; Muksin Muksin (Quality Education for All)
Purpose – This study aims to explore vocational education as stated in the basic constitution, law, government and ministerial regulations in the Indonesian context. This study aims to outline the Indonesian vocational education paradigm based on regulatory documents. Design/methodology/approach – This research uses a qualitative document analysis approach by extracting vocational themes regarding senior high school and higher education from the available documents. The keywords used for document document analysis are education, vocational school and vocational higher education. These words are forced to be used to distinguish the types and levels that exist in Indonesian education. Findings – The findings of this study identified that the political paradigms of vocational education, such as equality and justice, naming (regulative), purpose and life skills, the curriculum of local cultural value, decentralized authority, link and match and future paradigms are important themes raised in this study. This is a study to explore the politics of Vocational High School and Vocational Higher Education in Indonesia. Research limitations/implications – The vocational education policy documents in Indonesia that were analyzed may have been forgotten. As a result, the forgotten documents are not included in the analysis document. Forgotten interpretations and documents are part of the limitations of this research. Practical implications – It is hoped that the findings of this research will have an impact on improving vocational education policies in Indonesia. This can also be a comparison for other countries in looking at vocational education paradigms and policies. In general, these research findings can help in improving vocational education policies. However, this research still has limitations in terms of the number of documents analyzed. Originality/value – This study contributes to the promotion and political debate of vocational education nationally and internationally. The study further explores how interest groups are taking a role in achieving Vocational High School and Vocational Higher Education policies that are compatible with today’s needs and demands.